Parenting Style and Learning Achievement of Students in Kemayoran 1 Elementary School, Surabaya - Bambang Heriyanto; Dyah Wijayanti (Alliance oh Health Activists (AloHA), 2019)
Education for children is very important because to determine the results of student achievement in school must be of good value, but there are still some students whose learning achievements are decreasing so that parenting is needed. The purpose of this study was to determine the effect of authoritarian and democratic parenting on student achievement. Analytical research design with a population of class IV students amounted to 34 students and the sample was part of the fourth grade students as many as 26 students. The sampling method uses Simple Random Sampling technique. Independent variables are authoritarian and democratic parenting, while the dependent variable is learning achievement. Data collection used questionnaires and data analysis using Chisquare test. The results of research on authoritarian majority parenting were 14 with very good learning achievement 1 (7.1%), good learning achievement 13 (92.9%). And 12 parents with democratic parenting obtained good learning achievement 8 (66.7%), and enough learning achievement 4 (33.7%). The p-value was 0.048 (